2005
DOI: 10.1021/ja043697n
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium(II)-Catalyzed Hydrogenation of Carbon Dioxide to Formic Acid. Theoretical Study of Real Catalyst, Ligand Effects, and Solvation Effects

Abstract: Ruthenium-catalyzed hydrogenation of carbon dioxide to formic acid was theoretically investigated with DFT and MP4(SDQ) methods, where a real catalyst, cis-Ru(H)2(PMe3)3, was employed in calculations and compared with a model catalyst, cis-Ru(H)2(PH3)3. Significant differences between the real and model systems are observed in CO2 insertion into the Ru(II)-H bond, isomerization of a ruthenium(II) eta1-formate intermediate, and metathesis of the eta1-formate intermediate with a dihydrogen molecule. All these re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
118
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(129 citation statements)
references
References 55 publications
9
118
0
2
Order By: Relevance
“…For example, from a theoretical point of review, the rate-determining step is CO 2 insertion into a ruthenium hydride complex, which, in contrast, is a facile step in experimental studies. [292][293][294][295] Musashi and Sakaki presented a mechanistic investigation regarding the rhodium(III)-catalyzed CO 2 hydrogenation to formic acid. 296 The first step of the reaction is the insertion of CO 2 into the Rh(III)-H bond of the active species [RhH 2 (PH 3 ) 2 (H 2 O)] + .…”
Section: Mechanistic Understandingmentioning
confidence: 99%
“…For example, from a theoretical point of review, the rate-determining step is CO 2 insertion into a ruthenium hydride complex, which, in contrast, is a facile step in experimental studies. [292][293][294][295] Musashi and Sakaki presented a mechanistic investigation regarding the rhodium(III)-catalyzed CO 2 hydrogenation to formic acid. 296 The first step of the reaction is the insertion of CO 2 into the Rh(III)-H bond of the active species [RhH 2 (PH 3 ) 2 (H 2 O)] + .…”
Section: Mechanistic Understandingmentioning
confidence: 99%
“…Hence, elucidation of the pathways of formic acid formation is expected to lead to understanding of reaction systems in which CO 2 and H 2 are involved and also explain effects of different ligands and additives. Theoretical investigations have so far concluded that CO 2 insertion is the rate-limiting step [20,21] or that the reaction rate does not depend on H 2 pressure, [22] in spite of the fact that strong dependence of the reaction rate on H 2 pressure has been reported for homogeneous [12,15,23] and immobilized heterogeneous catalysts. [24] Results and Discussion State of [RuA C H T U N G T R E N N U N G (dmpe) 2 H 2 ] in toluene: Figure 1 shows the IR spectrum of [RuA C H T U N G T R E N N U N G (dmpe) 2 H 2 ] in toluene at 300 K and calculated spectra of cis-and trans-[RuH 2 ] complexes (from here on (dmpe) 2 is omitted).…”
Section: A C H T U N G T R E N N U N G (Ocho) 2 ] and Trans-[ru-a C Hmentioning
confidence: 99%
“…2 A significant number of studies exist in the literature regarding the adsorption, activation, and conversion of CO 2 using both heterogeneous, e.g., on metal/metal oxide surfaces [8][9][10][11] or metal-organic frameworks, [12][13][14][15] and homogeneous reactions, e.g., transition metal complexes. [16][17][18][19][20][21] More recently, transition metal sulfides have attracted significant attention for catalytic applications owing to their low cost, natural abundance, and prominent catalytic features. MoS 2 for instance has been widely used as an efficient catalyst for water splitting 22,23 and hydrodesulphurization, 24,25 whereas a recent report has shown its superior CO 2 reduction performance in an ionic liquid, compared to the noble metals, with a a) Electronic addresses: N.Y.Dzade@uu.nl and N.H.Deleeuw@uu.nl high current density and low overpotential (54 mV).…”
Section: Introductionmentioning
confidence: 99%